Beyond Sharia Compliance: Shifting Muslim Consumer Expectations and the Strategic Response of the Global Halal Industry - Razali, Ramadhan; Ulfah, Almira Keumala; Ismail, Sherif Mohamed A.; Lulaj, Enkeleda (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2026)
Background: The global halal industry is undergoing a paradigm shift driven by evolving Muslim consumer behaviors that increasingly intersect with sustainability and digital transformation. Despite its growth, a significant gap persists between conventional sharia compliance and modern expectations for ethical transparency. Objective: This study aims to identify shifting patterns in Muslim consumer behavior, analyze the gap between consumer expectations and industry capacity, and formulate adaptive strategies—specifically focusing on digitalization and regulatory harmonization within the ASEAN context. Methodology: A qualitative approach was employed, integrating a comprehensive literature review with in-depth, semi-structured interviews with 25 key informants. Participants included Muslim consumers (aged 18–45) from Indonesia, Malaysia, the UK, and Japan, alongside industry actors and policymakers. Data were analyzed using thematic content analysis to capture nuanced perspectives on halal-ṭayyib and global business ethics. Findings: The results reveal three critical dimensions for the industry’s future: (1) a shift in consumer demand toward halal-ṭayyib, encompassing quality and global ethical standards; (2) the pivotal role of digital technologies, such as Blockchain and IoT, in enhancing supply chain traceability; and (3) the urgent need for international regulatory harmonization, exemplified by the proposed Halal Industry Administration (HIA) in the Philippines. Conclusion: This study contributes to theoretical discourse by integrating Islamic consumption patterns with Institutional Theory and sustainability frameworks. It asserts that halal governance is a multidimensional construct in which Sharia integrity must align with global ESG (Environmental, Social, and Governance) principles.